Comparative study of surface, elemental, structural and optical morphologies of titanium dioxide-zinc oxide (TiO2-ZnO) and titanium dioxide-zinc oxide/graphene (TiO2-ZnO/Gn). (2023) - Harrum, W. M.W.; Akhir, R.M.; Afaah, A.N.; Eswar, K.A.; Husairi, F.S.; Rusop, M.; Khusaimi, Z.
Abstract: The aim of this study is to synthesize a highly dense nanosized TiO2 -ZnO sample with graphene (TiO2 -ZnO/Gn) thin film via solution immersion method and compare its properties with TiO2 -ZnO thin film without graphene. To prepare the titanium dioxide solution, the titanium butoxide precursor was added to ethanol, glacial acetic acid and triton-x-100 with a drop of deionized water. Next, to prepare for the ZnO/Gn solution, the zinc nitrate hexahydrate was added to hexamethylenetetramine (HMTA). Then, a specific weight of graphene was added into the solution before left for ageing. The thin films will be characterized in order to consider and enhance the potential of TiO2 -ZnO/Gn thin film in treating wastewater. Ultra-Violet Visible spectroscopy (UV–vis), X-ray Diffraction (XRD), and Field Emission Scanning Electron Microscopy (FESEM) were used to determine the optical, structural and morphological properties of the samples. From the UV–vis absorption spectra, the TiO2 -ZnO/Gn shows the better UV–vis performance compared to the TiO2 -ZnO sample. While the FESEM images for TiO2 -ZnO/Gn confirmed the presence of the Gn deposited on the thin film with specific grain-like structures of TiO2, hexagonal nanorod ZnO and wrinkles shape of Gn. Finally, the XRD analysis confirmed the crystallinity of the samples, and the elements present on the glass substrate. It has shown that there are TiO2, ZnO and Gn peaks present in the XRD patterns. Thus, TiO2 -ZnO/Gn is the best candidate to be used as the photocatalyst in treating the wastewater.